Bangkit Lebih Cepat: Melalui Program Pendampingan SDM dan Perencanaan Usaha Dengan Memanfaatkan Aplikasi Marketplace di Masa Pasca Pandemi Covid-19 pada Toko Sembako “Winda Jaya” Surabaya - Suryati Eko Putro; Novie Noordiana R.Y; Totok Mardianto; Arlisa Indriawati; Siti Khasanaturrohmah; Yeriko Yosua A (Jurnal Informasi Pengabdian Masyarakat, 2023)
As a result of the Covid-19 pandemic that hit Indonesia in 2020, it has resulted in a decline in the economy and activities in various sectors and regions of Indonesia. In 2023, the economic condition, which was in shock due to the Covid-19 pandemic, is gradually improving in line with the stability of the domestic financial market and the stretching of several economic sectors. The Government of Indonesia has declared that this year our economy must recover more quickly by making policy steps to strengthen the economy accompanied by transparent prioritization and proper policy coordination and synchronization. The community service team at the Faculty of Economics and Business, Surabaya University of Technology feels compelled to participate in the success of government programs by creating HR assistance programs and business planning by utilizing marketplace applications in the post-Covid-19 pandemic for business development and increasing sales turnover. The accompanying partner this time is the "Winda Jaya" Surabaya staple food shop, which sells various basic household needs such as rice, sugar, coffee and others. The community service team at the Faculty of Economics and Business tries to identify problems based on the collected data. After further analysis, the community service team formulated the problem as follows: (1) Lack of partner's understanding of management functions and how to manage HR, (2) Lack of partner's understanding of making good business plans, (3) Partner's lack of understanding about tips and tricks for successfully utilizing marketplace applications. The method used is divided into 3 (three) stages, namely the preparation stage, the activity implementation stage and the closing stage. The results of this community service activity are an increase in understanding by companion partners of management science material, procedures for managing human resources, making a good business plan and how to use marketplace applications for business development. This community service activity (PkM) is in the framework of implementing the Tridharma of Higher Education and also supports the Surabaya City Development Synergy Program